Local Versus Systemic Influences on Uterine Vascular Reactivity During Pregnancy in the Single-Horn Gravid Rat - Fuller, Robert (SAGE Publications, 2011)
This study was conducted to determine whether gestational changes in maternal uterine artery reactivity are primarily driven by local vs. systemic factors. Rats underwent surgical ligation of one oviduct, thereby restricting implantation and pregnancy to one uterine horn while maintaining a gestational endocrine milieu. Uterine arcuate arteries were isolated and cannulated to evaluate reactivity. Vessels from the implanted horn were significantly more sensitive to phenylephrine and less sensitive to sodium nitroprusside than those from the non-implanted horn; endothelial basal calcium levels were only increased in the implanted horn. Conversely, there were no differences in sensitivity to acetylcholine, or its effects on endothelial cell calcium, although efficacy was greater in vessels from the implanted vs. non-implanted horn. These findings demonstrate that local factors are predominant in inducing changes in vascular smooth muscle function, while endothelial adaptations result from an interplay between local and systemic factors, with distinct effects attributable to each.